Sucrose drinking mimics effects of nucleus accumbens µ-opioid receptor stimulation on fat intake and brain c-Fos-expression. (2nd November 2022) - Koekkoek, L.L.; Masís-Vargas, A.; Kool, T.; Eggels, L.; van der Gun, L.L.; Lamuadni, K.; Slomp, M.; Diepenbroek, C.; Kalsbeek, A.; la Fleur, S.E.
ABSTRACT: Objectives : We have previously shown that the combined consumption of fat and a sucrose solution induces overeating, and there is evidence indicating that sucrose drinking directly stimulates fat intake. One neurochemical pathway by which sucrose may enhance fat intake is through the release of endogenous opioids in the nucleus accumbens (NAC). Methods : To test this hypothesis, we provided rats with a free-choice high-fat diet for two weeks. During the second week, rats had access to an additional bottle of water or a 30% sucrose solution for five minutes per day. After these two weeks, we infused vehicle or the μ-opioid receptor agonist [D-Ala2, N-MePhe4, Gly-ol]-enkephalin (DAMGO) into the NAC 30 min after their daily access to the additional bottle of water or the sucrose solution. Results : Sucrose drinking had two effects, (1) it stimulated fat intake in the absence of DAMGO infusion, (2) it diminished sensitivity to DAMGO, as it prevented the rapid increase in fat intake typically seen upon DAMGO infusion in the nucleus accumbens. In a second experiment, we confirmed that these results are not due to the ingested calories of the sucrose solution. Lastly, we investigated which brain areas are involved in the observed effects on fat intake by assessing c-Fos-expression in brain areas previously linked to DAMGO's effects on food intake. Both intra-NAC DAMGO infusion and sucrose consumption in the absence of DAMGO infusion had no effect on c-Fos-expression in orexin neurons and the central amygdala but increased c-Fos-expression in the NAC as well as the basolateral amygdala. Discussion : In conclusion, we confirm that sucrose drinking stimulates fat intake, likely through the release of endogenous opioids. GRAPHICAL ABSTRACT: UF0001